The Relationship Between Teacher Creativity and Parenting Activities with Motivation to Learn Islam - Suharyat, Yayat; Sri Supriatin; Pauzan Haryono (Journal of Education Research, 2023)
Islamic religious education or PAI is important to be given from an early age so that children grow up with noble character and practice the teachings of Islam from its main source, namely the holy book Al-Qur'an and Sunnah. For that, every child is expected to study it seriously. This earnest effort begins with a positive motivation or encouragement from students to want to learn. This study aims to determine the relationship between teacher creativity and parenting activities with students' motivation to learn Islam. The research is quantitative associative with survey method and correlation design. This research was conducted in four IT Elementary Schools (SD) in three clusters of North Tambun, Bekasi. The four IT Elementary Schools are Ibnu Rusyd IT Elementary, Insan Mulia IT Elementary, IT Iskandar Muda Elementary School and IT Hasani Elementary School. The sample in this study were students in grades four and five, namely one hundred and fifty four students obtained by random cluster sampling technique. The study results show a positive and significant relationship between students' perceptions of teacher creativity and parenting activities and students' PAI learning motivation.